Significant Effect of Project Based Learning Video on Students’ Listening Skill in Pandemic Situation - Febiyanti, Ni Wayan; Nitiasih, Putu Kerti; Budiarta, Luh Gd Rahayu; Adnyayanti, Ni Luh Putu Era (Universitas Pendidikan Ganesha, 2021)
Listening is one of the most important language skills to be learned by students. However, it is very difficult for teachers to teach these skills in learning during the Covid-19 pandemic. Teachers need innovative teaching techniques, one of which is using video media. This study aims to investigate the impact of using project-based learning videos on students' listening comprehension skills. The population in this study involved 4th grade elementary school students. The sample in this study used 40 grade 4 students from one intact class that were selected with a specific purpose. This research includes quantitative research with one group pretest-posttest design. The data collection instrument in this study used a listening comprehension test and a listening comprehension assessment rubric. The data collected were analyzed using descriptive and inferential statistical analysis. From the results of the study, it was found that the mean value of the group at the posttest was 86.85 which was greater than the mean value at the pretest, which was 75.75. The standard deviation on the pretest also shows a value of 5,678 and the standard deviation on the posttest is 3,180. From the results of statistical inferential analysis shows that the value of Sig. (2-tailed) is .000. and lower than Sig. levels (.05). Therefore, it can be concluded that there is a significant impact on the use of project-based learning videos on students' listening comprehension during the covid-19 pandemic.